Efektivitas Cooverative Learning Terhadap Pembelajaran Kaidah Bahasa Arab menggunakan Kitab Silsilah Ta’limil Lughotil Arabiyyah - Arwadi; Ahmad Tarmizi; Muhammad Alfath Qaaf (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the effectiveness of Cooperative Learning in teaching Arabic grammar using the Silsilah Ta’limil Lughotil Arabiyyah book at Ma’had Zaadul Ma’ad Palembang. The study used a mixed-method approach with a sequential explanatory design, involving quantitative tests (pre-test and post-test), N-Gain analysis, as well as qualitative data from observation, interviews, and documentation. The results indicate that the implementation of Cooperative Learning significantly improved post-test scores of the experimental class (mean 89.78%) compared to the control class (75.21%), with an average N-Gain of 75% (moderately effective) compared to 47% in the control class (less effective). Qualitative findings show increased student participation, interaction, and active engagement in understanding Arabic grammar. Therefore, Cooperative Learning proves effective in enhancing Arabic grammar comprehension and can serve as an alternative, more interactive, and participatory.